Serum endocan levels in relation to traditional and non-traditional anthropometric indices in adult population: Endocan and obesity indexes - Klisic, Aleksandra; Kavaric, Nebojsa; Spasojevic-Kalimanovska, Vesna; Kotur-Stevuljevic, Jelena; Ninic, Ana (Journal of Medical Biochemistry, 2020)
Background and Aim: Association between endocan and non-traditional anthropometric indices, as distinct cardiovascular disease risk factors, has not been examined in previous studies. Endocan is a novel inflammation biomarker with its higher levels involved in cardiometabolic diseases development. Taking into consideration that obesity is an independent risk factor for many cardiometabolic diseases, we aimed to explore the relationship between endocan levels and novel anthropometric indices [i.e., body adiposity index (BAI), cardiometabolic index (CMI), a body shape index, body roundness index, conicity index, lipid accumulation product index and visceral adiposity index] and traditional ones [i.e., waist circumference, hip circumference, body mass index, waist-to-height ratio and waist-to-hip ratio] in adult population. Methods: A total of 177 participants were included. Anthropometric indices and biochemical parametres were measured. Results: Univariate regression analysis demonstrated positive correlations of endocan and almost all anthropometric data. To explore independent associations of endocan and anthropometric parameters, the Model which fulfilled criteria for ordinal regression testing was created. Adjusted odds for BAI given in the Model (OR=1.120, 95% CI 1.036-1.212, P=0.004), demonstrated that a rise in BAI by 1 unit increased the probability of higher endocan concentration by 12%. As well, a rise in CMI for 1 unit, increased probability for higher endocan levels for 2.6 times (OR=2.599, 95% CI 1.006-6.712, P=0.049). A total of 20.1% of variation in endocan levels could be explained by this Model. Conclusion: Non-traditional obesity indices, BAI and CMI independently correlated with higher serum endocan levels in adult population.